While allied health students prefer face-to-face clinical placement, telehealth can support competency development: results from a mixed-methods study - Bacon, Rachel; Hopkins, Sian; Georgousopoulou, Ekavi; Nahon, Irmina; Hilly, Catherine; Millar, CaraJane; Flynn, Allyson; Smillie, Linda; Chapman, Sarah; Brown, Nicholas (Frontiers in Medicine, 2023)
Introduction: Student clinical placements are a mandatory requirement within most accredited health programs. During the COVID-19 pandemic, many health settings that had traditionally provided placements cancelled their offerings. Telehealth services however, increased and emerged as an alternative placement setting. Aim: To compare the learning experiences for allied health students provided by telehealth and face-to-face accredited health placements. Methods: Health students, from a university clinic between March to December 2020, delivering both face-to-face and telehealth consultations, were invited to complete a telephone survey with 3 demographic questions; and 10-items comparing their telehealth and face-to-face learning experiences. Pearson’s Chi-squared / Fisher’s exact test was used to examine the association between each item and consultation setting. Qualitative survey data was thematically analysed using a descriptive approach. Results: 49 students from 2 universities and 5 disciplines completed the survey. Students rated their face-to-face experiences significantly higher than their telehealth experiences across all items (all p-vales <0.01). Across 9 items students reported positive learning experiences in both settings. Students had greater opportunities to work in a multidisciplinary team in a face-to-face setting. Four themes were generated: (1) placements can vary in quality regardless of setting; (2) telehealth can provide valuable learning experiences and support competency development; (3) enablers for telehealth placements and (4) barriers for telehealth placements. Conclusion: While telehealth can support student learning and competency development, in this study students preferred face-to-face experiences. To optimise telehealth placements consideration needs to be given to barriers and enablers such as technological issues and university curricula preparation.